Examining the impact of learning motivation, desire to work, and curiosity of students in the post-COVID-19 pandemic era - Syukur, Yarmis; Afdal, Afdal; Fikri, Miftahul; Zahri, Triave Nuzila; Anggraini, Osy Khalisyah (Journal of Education and Learning (EduLearn), 2025)
This research aims to examine the influence of learning motivation based on environmental conditions, desire to work, and main desires. To achieve this, a quantitative research design was used, and a total of 500 students (101 boys and 399 girls) in Indonesia were selected as respondents using proportional random sampling techniques. Data collection was carried out using a learning motivation scale questionnaire. The results showed that students had a high level of motivation, with an average score of 50.8. The desire to work can be seen from hopes and dreams, as well as a conducive environment. It is known that external factors such as encouragement from others and involvement in activities have a greater influence with significance scores of 0.801 and 0.766 respectively. Meanwhile, appreciation and hopes or aspirations each received a score of 0.709 and 0.704. This implies that encouragement and activity can be integrated into the student's self. The research also shows that gender does not have a significant effect on the desire to learn. However, providing appropriate encouragement and rewards will increase students' willingness to learn, which can be maintained by educational institutions and parents and instill a desire for personal progress and development.